Efforts To Develop Gross Motor Skills Through Penguin Gymnastics at Al-Madani Hafidz Ridho Kindergarten: Upaya Pengembangan Keterampilan Motorik Kasar Melalui Senam Pinguin di TK Al-Madani Hafidz Ridho - Adawiyah Harahap, Yuliatil; Sharfina, Dirayati; Leini Saragih , Srimis; Idris, Syamsul (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Al-Madani Hafidz Ridho Kindergarten is one of the kindergartens in Deli Serdang Regency. Children who study at Al-Madani Hafidz Ridho Kindergarten are aged 4 to 6 years. Children at this age are still called the golden period, whose physical condition and abilities in all things develop very quickly. One of the rapid developments in children aged 4-5 years is motor development, especially gross motor skills. Gymnastics is a physical activity that can help optimize children's development. Penguin gymnastics was chosen because there are not many difficult movements and are easier for children aged 4-6 years. With funny music and movements that depict penguins, children become happier and more entertained so that children do not feel burdened in following this gymnastics. This activity aims to teach penguin gymnastics to teachers and children of Al-Madani Hafidz Ridho Kindergarten. The stages carried out start from 1) Obtaining permission from the school as a partner in this community service, 2) Demonstrating the movements that will be done without music, 3) Performing the movements with music and repeating them 2 times, 4) Conducting an evaluation of the activity by asking students and teachers to demonstrate the movements that have been taught themselves, and 5) conducting follow-up activities so that this penguin gymnastics can become a daily routine before starting learning in class.